The Investment Strategy of With-Profits Life Insurance Firms - Jaafar, Karim Chawki (2008)
Abstract Within the context of an increasingly fragile life insurance industry, this paper conducts a quantitative investigation on the determinants of investment strategy within with profit life assurers in the UK, a dominant segment within the global industry. Examining a range of possible defining characteristics on investment strategy of such firms including size, financial strength (solvency), proprietary/mutual status, open/closed status and the level of guaranteed liabilities, the paper attempts to unravel the key influences on investment strategy as mapped out by an expanded set of investment risk indicators, such as the Equity Backing Ratio, Property Backing ratio, Non Approved Bonds Ratio and the Average Credit Rating of the bond portfolio. Having briefly collated the diverse academic literature on this subject, the paper uses a current dataset involving thirteen years worth of data from 1995-2007 sourced through SynThesys, in order to validate the research hypotheses. Splitting the analysis in two time intervals, one involving the full 13 year period and the other involving the years 2005-2007 post the new regulations, it finds that investment strategy is indeed significantly influenced by the defining characteristics of the firm albeit it in a complex way. While some relationships between these variables are straightforward, others present complex pictures requiring further explanation and research. In particular, the paper finds that larger, more solvent and open firms do tend to invest higher proportions in risky assets such as equity and property. It also contradicts to some degree, earlier findings that property and equities are viewed as competitive assets, finding instead that there are some complementarities between them.